Consumer Legal Protection in Electronic Commerce Transactions - Meyke Alvianieta Ali (Universitas Negeri Gorontalo, 2019)
Abstract: The purpose of this study is to find out how the legal protection for consumers against third parties' formal legal in electronic commerce transactions. The research method of this thesis uses a normative legal research method. , and the imposition of sanctions on business actors in the event of a violation. The form of responsibility for the Shopee site manager can be reflected in the provision of compensation through refunds, personal data protection, consumer reporting facilities, but Shopee also has limitations on liability. Keywords: Consumers, Electronics, Legal Protection, Trade Transactions